Overcoming aggression: musing on mindfulness and self-control - Yusainy, Cleoputri (2013)
The ability to restrain oneself from acting on aggressive impulses is arguably a crucial aspect of human functioning and interaction. Yet growing evidence in the literature suggests that people’s self-control resources may be limited and, at times, self-controlled regulation could even increase the association between aggressive triggers and aggressive behaviour. As an alternative, mindfulness practices encourage individuals to be aware and accept their aggression-related thoughts and emotions simply as an ephemeral state rather than to control them.